Contributions of integrated soil fertility management (ISFM) to various sustainable intensification impact domains in Tanzania - Kihara, Job Maguta; Manda, J.; Kimaro, Anthony A.; Swai, E.; Mutungi, C.; Kinyua, M.; Okori, Patrick; Fischer, Gundula; Kizito, Fred; Bekunda, Mateete A. (Elsevier, 2022)
CONTEXT The implementation of integrated soil fertility management (ISFM) varies widely among farmers, from no ISFM to multiple computations of ISFM components (i.e., improved germplasm, organic resources, fertilizers, and local adaptations e.g., soil and water conservation (SWC)). There is no comprehensive report on farmers' use of ISFM components and their impact on sustainable intensification domains of productivity, economic, social, human condition, and environment and the associated variations across farmer fields and agro-ecological zones (AEZs).